GRDP, Regional Spending, and Inflation as Drivers of People’s Purchasing Power - Masulliya, Fadilla; Syafitri, Wildan (Journal of Development Economic and Social Studies, 2026)
Purchasing power reflects economic welfare because it indicates households' ability to meet their needs. In East Java Province, GRDP, inflation, and regional spending fluctuated during the 2019–2024 period, creating disparities in purchasing power between districts/cities that need to be analyzed further. This study aims to analyze the effect of GRDP, regional spending, and inflation on purchasing power in East Java using district/city-level panel data through a quantitative approach, and includes a Covid-19 dummy control variable to capture the impact of the pandemic on regional economic conditions. The results show that GRDP has a positive and significant effect on people's purchasing power. Regional spending also has a positive and significant effect on people's purchasing power. Conversely, inflation does not have a significant effect on people's purchasing power, indicating that during the study period, the inflation rate was relatively stable and did not significantly affect household consumption. These findings confirm that people's purchasing power in East Java is more sensitive to changes in income and fiscal policy than to price pressures.